UTILIZATION OF POLYPROPYLENE IN BITUMINOUS CONCRETE - EZEMENIKE CHUKWUKA; OLADELE ISIAKA; ADERINLEWO OLUFIKAYO; OYEDEPO OLUGBENGA (Journal of Engineering Studies and Research)
The utilization of polypropylene in form of waste plastic to produce bituminous concrete for pavement construction was studied. The aggregates, bitumen and polypropylene were characterized. Bitumen was partially replaced with polypropylene at 2, 4, 6 and 8% by weight to produce asphalt concrete, thereafter, Marshal Stability and flow test was carried out on asphalt concrete. From the result, Marshal Stability values of 8.77, 9.18, 9.5 and 11.51 KN while flow values of 3.5, 3.2, 3.1 and 2.8 mm were respectively obtained. This study suggests that the polypropylene could enhance the performance of asphalt concrete and decrease the cost of road construction.